IS PAKISTAN STOCK MARKET EFFICIENT? (A COMPREHENSIVE STUDY ON PAKISTAN STOCK EXCHANGE) - Malik, Muhammad Shaukat; Munir, Samavia; Waheed, Noorulain (International Journal of Research -GRANTHAALAYAH, 2017)
The purpose of this research is to find weak form of market efficiency of Pakistan stock exchange. Daily return of KSE-100 index was obtained during the time period of 2nd November 1991 to 28th may 2015. Total time span of the study was 23 years 6 month and 26 days. To examine the stationary in the data points three test named as Graphical Analysis, Autocorrelation Function (ACF) and The Unit Root Test were applied. After that ARIMA (1, 1, 2) model was applied and SPSS 21 used for data analysis. Results revealed that the Pakistan stock exchange not fulfill the necessary assumptions of weak form of market efficiency. Research findings would be beneficial for the individual investors as well as for the businesses as it guide individual investors for establishment of their investment portfolio and for businesses to get funds at appropriate cost. This research is valuable for the researchers as they can explore the current idea of research in other equity investment alternatives of Pakistan and also provide guideline for law regulatory authorities for establishment of laws and regulations of stock markets. This research work would be a valuable addition in the current literature as very few studies have been conducted in emerging stock markets.